2018
DOI: 10.1371/journal.pntd.0006589
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune receptors over expression correlate with chronic chagasic cardiomyopathy and digestive damage in patients

Abstract: Chronic chagasic cardiomyopathy (CCC) is observed in 30% to 50% of the individuals infected by Trypanosoma cruzi and heart failure is the important cause of death among patients in the chronic phase of Chagas disease. Although some studies have elucidated the role of adaptive immune responses involving T and B lymphocytes in cardiac pathogenesis, the role of innate immunity receptors such as Toll-like receptors (TLRs) and Nod-like receptors (NLRs) in CCC pathophysiology has not yet been determined. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Pyroptosis plays a pivotal role in the pathogenesis of various CVDs and involves ECs, VSMCs and so on. This process occurs in patients suffering from myocardial infarction (MI), hypertension and cardiomyopathy, as well as in animal models of ischaemia–reperfusion injury (IRI), atherosclerosis (As), heart failure (HF) and cardiomyopathy . Pyroptosis is a highly regulated cell death process, and inhibition of this process by pharmacological or genetic intervention is cardioprotective under many conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis plays a pivotal role in the pathogenesis of various CVDs and involves ECs, VSMCs and so on. This process occurs in patients suffering from myocardial infarction (MI), hypertension and cardiomyopathy, as well as in animal models of ischaemia–reperfusion injury (IRI), atherosclerosis (As), heart failure (HF) and cardiomyopathy . Pyroptosis is a highly regulated cell death process, and inhibition of this process by pharmacological or genetic intervention is cardioprotective under many conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Our group demonstrated increased of TLR8 and IFN-β expression in peripheral blood mononuclear cells of patients with digestive and cardiodigestive form of the disease [28]. TLRs activation leads NF-κB activation and production of inflammatory mediators, such as pro-IL1β, pro-IL-18, IL-6, IL-12 and TNF-α [29].…”
Section: Introductionmentioning
confidence: 72%
“…The authors suggested that these parasites may activate the host's innate immune response via different Toll-like receptors to protect cardiomyocytes from parasites. In contrast, Pereira et al [43] suggest that a high TLR2 expression in patients with chronic Chagas cardiomyopathy may induce an increase in IL-1β, IL-12, and TNF-α, thereby elevating cardiac in ammation and contributing to heart dysfunction. Oliveira et al [44] observed that a de ciency of TLR4 leads mice to being more susceptible to T. cruzi infection, as evidenced by a higher parasitemia and earlier mortality.…”
Section: Discussionmentioning
confidence: 90%